Long-term effects of pediatric adenotonsillectomy on serum immunoglobulin levels: results of a randomized controlled trial - van den Akker, Emma H; Sanders, Elisabeth A M; van Staaij, Birgit K; Rijkers, Ger T; Rovers, Maroeska M; Hoes, Arno W; Schilder, Anne G M (Annals of allergy, asthma, & immunology, 2006)
It remains controversial whether pediatric adenotonsillectomy ultimately results in decreased serum immunoglobulin levels and if so whether such a decrease is associated with increased susceptibility to upper respiratory tract infections (URIs). To evaluate changes in serum immunoglobulin levels in relation to occurrence of URIs in children participating in a randomized controlled trial on the effectiveness of adenotonsillectomy. A total of 300 children aged 2 to 8 years, with symptoms of recurrent throat infections or tonsillar hypertrophy, were randomly assigned to either adenotonsillectomy or watchful waiting (WW). Serum samples were collected at baseline and at 1-year follow-up. Occurrence of throat infections and other URIs during first-year follow-up was recorded in a diary by the child's parents. Paired serum samples were available for 123 children (63 in the adenotonsillectomy group and 60 in the WW group). IgG1 and IgG2 levels decreased but remained within the reference range for age in both study arms. IgM and IgA levels decreased as well but remained elevated. The IgA level in the adenotonsillectomy group decreased in significantly greater degree compared with the WW group, but this difference disappeared in cases where children experienced frequent URIs. In general, no relation between immunoglobulin levels and the number of throat infections or URIs at 1-year follow-up was found. Immunoglobulin levels of children undergoing adenotonsillectomy decreased from elevated to slightly elevated or reference values for age during 1-year follow-up irrespective of treatment (adenotonsillectomy or WW). IgA showed a greater decrease in the adenotonsillectomy group but rose to levels comparable with the WW group in cases of frequent URIs. This finding indicates that the remaining mucosa-associated lymphoid tissue can compensate for the loss of tonsil and adenoid tissue.